An Analysis of the Critical Success Factors of Social Businesses Applied to Agribusiness: A multi-cases study (Research, Society and Development, 2020)
Family farming has a history of dependence on public policies and collects unsuccessful cases of associations and cooperatives. At the same time, sustainable agriculture or intensive agriculture emerges as an important trend, but also a challenge for all rural producers.In this sense, the social entrepreneur, through the development and application of green technologies, appears as a partner to face the challenges of social inclusion and sustainability.This project seeks to discuss the critical factors of social business applied to agribusiness, considering both the business and family agriculture segment. To this end, the work uses bibliographic and documentary research as well as a multi-case study. Among the results, we can mention the critical success factors of the cases studied and the main characteristics that form the leadership profile of the entrepreneurs.